PEMBUATAN DAN UJI MUTU FISIK SEDIAAN FACE MIST EKSTRAK DAUN ALPUKAT (Persea americana Mill.) - Sukirawati; Burhamin, Yusriyani; Nur Afifah Kamas (Jurnal Kesehatan Yamasi Makassar, 2025)
Avocado leaves are known to contain various bioactive compounds such as flavonoids, saponins, tannins, alkaloids, and phenols that are beneficial for skin health. This study refers to several literatures indicating that avocado leaf extract (Persea americana Mill.) exhibits significant antioxidant and antibacterial activities, which is why it was used as the active ingredient in the preparation of face mist. The aim of this research was to determine the physical quality of face mist formulations made with avocado leaf extract at concentrations of 0% (F0), 5% (F1), 7.5% (F2), and 10% (F3). The study was conducted experimentally in the laboratory, where the avocado leaf extract was obtained through maceration using 96% ethanol as the solvent. Physical quality tests performed included organoleptic evaluation, homogeneity test, pH measurement, spray distribution test, drying time test, and viscosity test. The results showed that avocado leaf extract (Persea americana Mill.) can be formulated into face mist preparations at concentrations of 5%, 7.5%, and 10%, all of which met the physical quality standards for face mist products.